A Severity Score and Outcome Prediction in Patients that Suffered an Ischemic Stroke - Corina Roman-Filip; Maria-Gabriela Catană (Vlădoiu); Mădălina Văleanu; Romeo-Gabriel Mihăilă (Emergency Medicine International)
Background. Stroke is the main cause of disability and exitus worldwide. The prediction of mortality of this pathology represents a major challenge. More than that, the infection with the SARS-CoV-2 virus is a challenge for every clinician worldwide, and hypercoagulability is one of its biggest concerns that can lead to stroke. Objective. Our aim was to develop a severity stroke index for both SARS-CoV-2 stroke patients and noninfected stroke patients which we hope to be helpful in patient’s management. Methods. We conducted a prospective study during January 2021–June 2021 which included 80 patients who suffered an ischemic stroke, 40 of which had both stroke and SARS-CoV-2 infection. We have established a panel of biomarkers including CRP, IL-6, fibrinogen, ESR, D-dimer, leucocytes, lymphocytes, and NLR and compared the results of our two cohorts. Results. SARS-CoV-2 stroke patients have experienced elevated levels of biomarkers that rise in inflammation such as hs-CRP, IL-6, and D-dimer, comparing to noninfected stroke patients. Also, the probability of exitus in SARS-CoV-2 patients is 4.2 times higher than in noninfected subjects. With regard to stroke severity, we have concluded that a NIHSS score higher than 15 points considerably influences the death rate, the probability of exitus being 9.16 times higher than in NIHSS score lower than 15. Conclusion. Based on our result, we have established a severity score index which includes NIHSS score, age, gender, the presence/absence of COVID-19 infection, and the following biomarkers: hs-PCR, IL-6, D-dimer, fibrinogen, and ESR, which can be used as a tool to guide patient’s management.